Ecogenesis of ectoparasites of agricultural animals. - Pulatov F.S.; Rakhimov M.Yu; Ismoilov A.Sh; Boltaev D.M.; Saifiddinov B.F (Genius Journals, 2022)
The article presents information on the ekogenesis of harmful ektoparasites common among agricultural and in the areas of animal husbandry
Keywords: Ekogenes; еcotone; ecology; zoophile